ANALISIS TRANSFER PANAS MENYELURUH PADA SELUBUNG BANGUNAN DI DAERAH TROPIS - Annisa Dwi Hariyanti; Erni Setyowati; Gagoek Hardiman (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: The creation of architectural works in tropical climates must be appropriate and responsive to the climate. In its application, it is expected to comply with the criteria for green building design requirements in SNI 03-6389-2011 and Regulation of the Minister of Public Works and Public Housing Number: 21 of 2021 concerning Green Building Performance Assessment, namely that the overall heat transfer value of the building envelope does not exceed 35 W/m2. The choice of material used in the building envelope affects the amount of heat transfer value in a building. The building envelope of the Polytechnic of Furniture Industry and Wood Processing Campus Education Building on all four sides are dominated by Asahimas green stopsol reflective glass material with a glass thickness of 8 mm and conwood material in several parts. The amount of heat transfer value is analyzed using quantitative research methods with the calculation of OTTV (Overall Thermall Transfer Value). From the analysis, it is known that the overall OTTV value of the building is 54,94 W/m2, so it does not meet the criteria for green building design requirements. It is necessary to make retrofit design efforts to reduce the OTTV value in order to achieve OTTV value as mentioned in the SNI 03-6389-2011 and Regulation of the Minister of Public Works and Public Housing Number: 21 of 2021.Abstrak: Pembuatan karya arsitektur di iklim tropis harus tepat dan responsif terhadap iklim. Dalam penerapannya diharapkan sesuai dengan kriteria persyaratan perancangan bangunan hijau pada SNI 03-6389-2011 dan Permen PUPR RI Nomor: 21 Tahun 2021 tentang Penilaian Kinerja Bangunan Gedung Hijau, yaitu bahwa nilai transfer panas menyeluruh pada selubung bangunan tidak melebihi 35 W/m2. Pemilihan jenis material yang digunakan pada selubung bangunan berpengaruh terhadap nilai transfer panas pada suatu bangunan. Selubung bangunan Gedung Pendidikan Kampus Politeknik Industri Furnitur dan Pengolahan Kayu pada keempat sisinya didominasi material kaca reflektif stopsol green Asahimas dengan ketebalan kaca 8 mm dan material conwood di beberapa bagian. Untuk mengetahui besarnya nilai transfer panas dilakukan analisa menggunakan metode penelitian kuantitatif dengan perhitungan OTTV (Overall Thermall Transfer Value). Dari hasil analisa diketahui bahwa nilai OTTV keseluruhan bangunan sebesar 54,94 W/m2, sehingga tidak memenuhi kriteria persyaratan perancangan bangunan hijau. Perlu dilakukan upaya retrofit desain untuk menurunkan nilai OTTV tersebut agar mencapai nilai OTTV sesuai SNI 03-6389-2011 dan Permen PUPR RI Nomor: 21 Tahun 2021.